Rare late-presentation congenital diaphragmatic hernia mimicking a tension pneumothorax - Muhammad Zahid Abdul Muien, MD, DrRad; Kohila Jeyaprahasam, MBBS; Thiagu Krisnan, MBBS, MMed; Chiak Yot Ng, MBBS, MMed(Rad); Yong Guang Teh, MD, DrRad (Radiology Case Reports, 2021)
Congenital Diaphragmatic Hernia (CDH) is due to a defect in the diaphragm and is usually detected soon after birth. However, in rare cases, asymptomatic CDHs can be missed and present later in life. Late-presentation CDH can be misdiagnosed as tension pneumothorax leading to iatrogenic complications. We report a case of a 10-year-old boy who presented with non-specific symptoms of vomiting and occasional breathlessness, but was subsequently diagnosed as late-presentation CDH. This case highlights the role of imaging in the diagnosis and management of late-presenting CDH. The role of CT imaging as an invaluable tool to further evaluate equivocal radiographic findings in CDH is discussed.